Estimation of a variable rate of depreciation: A dummy variable approach - Ingmar R. Prucha (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
Many important economic problems require measures of physical and R&D capital. Except for some recent studies, there have been relatively few contributions in the literature that provide econometric estimates for the depreciation rates of physical and R&D capital. One reason for the relative paucity of such econometric studies may be that if the depreciation rates are viewed as unknown parameters, or as a functions of unknown parameters, then the corresponding stocks of physical and R&D capital are also unobserved, resulting in a formidable estimation problem. In the past econometric estimates of the depreciation rates of physical and R&D capital were typically obtained from self-programmed estimation algorithms. In this note we introduce an approach that permits the econometric estimation of constant and variable rates of depreciation of physical and R&D capital using standard econometric packages.
Keywords: 330; Bilanzielle Bewertung; Schätztheorie; Kapitalstock; Humankapital; Industrieforschung; Theorie